2019
DOI: 10.1002/acm2.12734
|View full text |Cite
|
Sign up to set email alerts
|

Signal and contrast to noise ratio evaluation of fluoroscopic loops for interventional fluoroscope quality control

Abstract: Modern fluoroscopes pose a challenge for the clinical physicist for annual testing and continued upkeep. These fluoroscopes are critical to providing care to patients for complex interventions, and continue to evolve in automated image quality adjustments. Few tools in software or hardware currently exist to assist the physicist or technologist in gauging fluoroscope constancy or readiness for procedures. Many modalities such as mammography, computed tomography or even magnetic resonance imaging are much more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The average SI values of the two observers were used in this study. The CR values of BME and the normal pedicle in spondylosis patients were calculated using the SI values of the spinal cord as per the following formulae [6][7][8]:…”
Section: Contrast Ratio On Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The average SI values of the two observers were used in this study. The CR values of BME and the normal pedicle in spondylosis patients were calculated using the SI values of the spinal cord as per the following formulae [6][7][8]:…”
Section: Contrast Ratio On Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, there is no proven quantitative method to evaluate BME on MRI for lumbar spondylolysis. In the field of radiology, the contrast ratio (CR) is reported as a quantitative parameter for the analyses of human tissues [7][8][9]. Although some studies have reported on the CR in the fields of pulmonary medicine and liver disease [10,11], few studies have reported on the CR in the field of the spine surgery [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a method often is described as a "double clutch" so that a possible spectral filter or other parameters may change as needed due to increased or different phantom loading. Goode et al [32] have been utilized 0.3 mm Cu spectral filter in a normal fluoro dose level and to reach a low dose setting with high beam quality, the copper spectral filter increased 0.6 mm besides lessening 5 mGy/min dose rate and growing kVp by 3. They indicated that the signal to noise ratio (SNR) is increased from normal to low dose level for a thickened phantom.…”
Section: Discussionmentioning
confidence: 99%
“…The SI values of the T2 high-intensity lesion (H) and the spinal cord (C) were used to calculate the signal ratio (SR) and contrast ratio (CR). The SR and CR were calculated according to the following formulae [16,17]:…”
Section: Signal Ratio and Contrast Ratio On Mrimentioning
confidence: 99%